Impact on poverty and income inequality in Malaysia’s economic growth - Islam, Rabiul; Abdul Ghani, Ahmad Bashawir; Zainal Abidin, Irwan Shah; Rayaiappan, Jeya Malar (LLC “СPС “Business Perspectives”, 2017)
Poverty and income inequality are extreme issues that still exist in Malaysia. Any rise in poverty and income inequality definitely affect economic growth. There are many great efforts taken by the government of Malaysia to eradicate poverty and to reduce the gap of income inequality which occurs since 1970’s. The incidence of poverty and income inequality is higher in rural areas compared to urban areas. This paper is mainly to study the level of poverty and income inequality in Malaysia together with government intervention to develop Malaysia’s economic growth. The research is focused among the working people at Ipoh, Perak. In this paper, questionnaire forms are being distributed to get information regarding the issue of poverty and income inequality. It also looks into the strategies taken by the government of Malaysia to eradicate poverty and income inequality. Few recommendations are given in terms of education policy, financial aid and assistance from government and non-government organization (NGO) to upgrade the standard and quality of living among the poor and lower-income group of people.